1,3,6,8-tetraazapyrenes: synthesis, solid-state structures, and properties as redox-active materials - Geib, Sonja; Martens-Kruck, Susanne; Lombeck, Florian; Wadepohl, Hubert; Gade, Lutz H. (The journal of organic chemistry, 2012)
A series of new tetraazapyrene (TAPy) derivatives has been synthesized by reducing 1,4,5,8-tetranitronaphthalene to its corresponding tin salt (I) and reacting it with perfluorinated alkyl or aryl anhydrides. The resulting 2,7-disubstituted TAPy molecules and the known parent compound 1,3,6,8-tetraazapyrene (II) have been further derivatized by core chlorination and bromination. The brominated compounds served as starting materials for Suzuki cross-coupling reactions with electron-poor arylboronic acids. Single-crystal X-ray analyses established polymorphism for some TAPy compounds. The ground-state geometries of all new TAPy derivatives were modeled with DFT methods [B3PW91/6-31 g(d,p) and B3PW91/6-311+g(d,p)], especially focusing on the energies of the lowest unoccupied molecular orbital (LUMO) and the electron affinities (EA) of the molecules. The results of the calculations were confirmed experimentally by cyclic voltammetry to evaluate the substitution effects at the 2 and 7 position and the core positions, respectively, and gave LUMO energy levels that range from −3.57 to −4.14 eV. Fabrication of organic field-effect transistors (OFETs) with several of these tetraazapyrenes established their potential as organic n-type semiconductors.
Gesehen am 26.04.2018